Spinal dural arteriovenous fistulas: evaluation with MR angiography. - Bowen, B C; Fraser, K; Kochan, J P; Pattany, P M; Green, B A; Quencer, R M (American Journal of Neuroradiology, 1995)
PURPOSE To show that postgadolinium three-dimensional time-of-flight MR angiography shows abnormal intradural vessels associated with spinal dural arteriovenous fistula better than routine MR imaging and provides screening information useful for subsequent diagnostic conventional angiography and/or posttreatment evaluation. METHODS Precontrast and postcontrast MR imaging and MR angiograms, as well as subsequent digital subtraction angiograms, were obtained for eight patients with dural arteriovenous fistulas, diagnosed with digital subtraction angiography and verified with surgery. In four patients, MR studies also were obtained after surgery. RESULTS All patients had cord hyperintensity of T2-weighted images and postgadolinium enhancement on T1-weighted images. Five had vessellike signal abnormalities in the subarachnoid space on MR. Abnormal intradural vessels were detected in all eight patients with MR angiography. Comparison with digital subtraction angiography revealed these vessels to be primarily enlarged veins of the coronal venous plexus on the cord surface. In six patients, the medullary vein draining the fistula was demonstrated, indicating the level of the fistula, later identified by digital subtraction angiography. After surgical obliteration of the fistula, the draining medullary vein and most or all of the abnormal coronal veins were no longer demonstrated, with decrease or resolution of cord hyperintensity on T2-weighted images. CONCLUSION Postgadolinium, spinal MR angiography in cases of suspected dural arteriovenous fistula provides information about intradural veins that supplements the diagnostic value of the MR imaging results, facilitates the subsequent digital subtraction angiography study, and, in treated cases, reflects the success of surgery and/or embolization.